Multibeam bathymetry raw data (Kongsberg EM 122 entire dataset) of RV METEOR during cruise M179/1 - Wollschläger, Jochen; Wölfl, Anne-Cathrin (PANGAEA, 2023)
Multibeam bathymetry raw data was recorded in the Atlantic during cruise M179/1 that took place between 2021-12-22 and 2022-01-12. The data was collected using the ship's own Kongsberg EM 122. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data (zip file) and the cruise report for details.